Prevalence of Pediculosis Capitis in Orphanages and Islamic Boarding Schools in the Surakarta - Setya, Adhi Kumoro; Haryatmi, Dwi (GLOBAL HEALTH SCIENCE GROUP, 2023)
Residential environments such as orphanages and identical boarding houses have quite high population densities. This makes cottages and orphanages vulnerable and has a high potential for transmission of Pediculus Humanus var. capitis causes the disease Pediculosis capitis. This disease is an indicator of poor personal hygiene and the environment in which one lives. The higher the case of tick infestation, the worse the surrounding community becomes. This study aims to determine the prevalence of cases of pediculosis capitis in Islamic boarding schools and orphanages in the Surakarta.This research uses a descriptive research design with purposive sampling technique. The samples analyzed were the hair and scalp areas of 155 child and adolescent respondents in Islamic boarding schools and orphanages in Surakarta City. The data obtained was carried out by laboratory examination in the form of egg, nymph and adult flea stages as well as questionnaires filled out by respondents using guided interviews in the form of data on respondents' characteristics and personal hygiene status obtained through scoring. The relationship between Personal Hygiene and the incidence of Pediculosis capitis was analyzed using the chi-square test. From the results of research conducted on all respondents who were willing and met the criteria, it was discovered that of the 155 respondents, 59 (38%) were positive for pediculosis capitis and 96 (62%) did not experience pediculosis capitis. Sequentially, the highest cases were found in locations; Laweyan sub-district orphanage (76.7%), city orphanage (60%), Pasar Kliwon Islamic boarding school (36%) and Laweyan orphanage (0%). The personal hygiene status of the respondents in this case was 81% good, while 19% had poor personal hygiene status. In all cases that were found to be positive for pediculosis capitis, all of them were found to be in the egg, nymph and adult stages. The highest characteristics of positive cases were found in respondents with straight hair and longer than shoulder length. From this research, it was concluded that there was a significant relationship between personal hygiene and the cases of pediculosis capitis found. The point prevalence of pediculosis capitis in Islamic boarding schools and orphanages in the city of Surakarta is 38% of cases. As many as 81% of respondents had good personal hygiene status and 19% of respondents had poor personal hygiene.